Urokinase Evaluated with the Experimental Radioactive Embolus - Hume, M (Thrombosis and Haemostasis, 1967)
Urokinase and urokinase-activated plasmin have been given to the dog and rabbit. A thrombolytic state has been induced. Purified urokinase has induced lysis of the experimental radioactive blood clot embolus in the circulation. Demonstration of effectiveness in this animal experiment is hampered by inhibition of the agents in the circulation to a degree much greater than was noted in previous experiments with streptokinase. In vitro testing indicates that under proper conditions urokinase will be an effective agent in the treatment of human thromboembolism.